Failure modes of API 12D tanks with a semicircular-topped rectangular cleanout and stepped shell design. (August 2018) - Azzuni, Eyas; Guzey, Sukru
Abstract: The American Petroleum Institute Specification 12D (API 12D) provides the oil and gas industry with ten tank designs with nominal capacities ranging from 500 bbl (79.5 m 3 ) to 10, 000 bbl (1590 m 3 ). These tanks serve as a temporary product storage medium at the upstream segment of the industry, and are mass-produced to accommodate the demand. The structural performance of these ten 12D tanks is assessed in this study to verify that safe operation is maintained under various loading conditions. This study investigates the behavior and performance of the API 12D tank designs with a new rectangular cleanout with a semicircular top that is surrounded by a reinforcement pad. Various loading patterns were modeled in a finite element analysis approach including internal pressure, vacuum, hydrostatic pressure, and wind load. An elastic stress analysis, an elastic-plastic stress analysis, and an elastic buckling analysis were used in this work to compare the behavior of the tank designs against the failure criteria specified for each type of analyses. The stress level, plastic strain, buckling load, and tank uplift are reported for each of the ten API 12D tank designs and possible shell thickness variations are provided as insight into the performance expected with the new cleanout detail. Highlights: Elastic stress analysis was used to evaluate the relative strength of the top and bottom joints. Elastic-plastic analysis considered stress redistribution and inelastic deformations. Wind load was applied to the models to study stress levels and bottom uplift. Eigenvalue buckling analysis was carried out to estimate the critical buckling modes of the tank. In general, buckling at roof-to-shell joint occurs before the shell-to-bottom joint buckles.